An Unknown Berlin Manuscript: Secere-yi Turfan Wang - Olmez, Zuhal; Mirsultan, Aysima (ISTANBUL UNIV, 2023)
In the second half of the 19th century, East Turkistan (Xinjiang Uyghur Autonomous Region) was a place where many religions and cultures coexisted and attracted the interest of travelers from all around the world. These travelers were motivated by the desire to delve into the unexplored language and culture of the Silk Road. One classic example of the efforts of Eastern scholars involved the four German (Prussian) Turfan expeditions known from 1902-1914. The primary goal of these expeditions was to obtain Buddhist artifacts as well as other cultural relics and written records from pre-Islamic Central Asia. Albert von Le Coq (1860-1930) led the second and fourth expeditions and acquired many friends in the region. Among the notable figures in the local aristocracy was Emin Khwaja Wang (1885-1933) from Lukchun, Turfan. The manuscript this article evaluates delves into the genealogy of the Wang family in Turfan, spanning from Feridun Wang to Emin Wang. This manuscript, referred to as Manuscript Arab 4, is currently housed in the Turfan Room of the Oriental Department at the Berlin State Library (Staatsbibliothek zu Berlin). It had likely been brought to Berlin during the German Turfan expeditions. This study provides an introduction tothe Wang family in Turfan and presents additional sources related to their history, a copy of the manuscript, and insights into its linguistic characteristics. It also includes a transcription of the text into Turkish and an index/glossary of select words. This primary source document from the period allows valuable information to be gained about Wang's empire in Turfan.
Keywords: East Turkistan; Turfan; Turfan Kingdom; Emin Wang; German Turfan expeditions; Linguistics; Literature